Impact of sex on the adaptation of adult mice to long consumption of sweet-fat diet - N. M. Bazhan; T. V. Iakovleva; A. D. Dubinina; E. N. Makarova (Вавиловский журнал генетики и селекции)
In rodents, the most adequate model of human diet-induced obesity is obesity caused by the consumption of a sweet-fat diet (SFD), which causes more pronounced adiposity in females than in males. The aim of this work was to determine the sex-associated effect of SFD on the expression of genes related to carbohydrate-lipid metabolism in adult mice. For 10 weeks, male and female С57Bl mice were fed a standard laboratory chow (Control group) or a diet, which consisted of laboratory chow supplemented with sweet cookies, sunflower seeds and lard (SFD group). Weights of body, liver and fat depots, blood concentrations of hormones and metabolites, liver fat, and mRNA levels of genes involved in regulation of energy metabolism in the liver, perigonadal and subcutaneous white adipose tissue (pgWAT, scWAT) and brown adipose tissue (BAT) were measured. SFD increased body weight and insulin resistance in mice of both sexes. Female mice that consumed SFD (SFD females) had a greater increase in adiposity than SFD males. SFD females showed a decreased expression of genes related to lipogenesis (Lpl) and glucose metabolism (G6pc, Pklr) in liver, as well as lipogenesis (Lpl, Slca4) and lipolysis (Lipe) in pgWAT, suggesting reduced energy expenditure. In contrast, SFD males showed increased lean mass gain, plasma insulin and FGF21 levels, expressions of Cpt1α gene in pgWAT and scWAT and Pklr gene in liver, suggesting enhanced lipid and glucose oxidation in these organs. Thus, in mice, there are sex-dependent differences in adaptation to SFD at the transcriptional level, which can help to explain higher adiposity in females under SFD consumtion.